Model Hubungan Karakteristik Arus Lalu Lintas Pada Ruas Jalan Abdullah Silondae Kota Kendari - Florentinus, La Derita; Lakawa, Irwan; Sulaiman, Sulaiman (Universitas Sulawesi Tenggara, 2021)
Abdullah Silondae Road is a type of 4 lane 2 undivided road (4/2 UD) which is a pathway to urban activities, education, trade and. The research objective is to model the relationship of traffic characteristic parameters on the Abdullah Silondae Road section based on traffic studies, including studio volumes and vehicle speeds which are classified into three groups namely motorcycles (MC), light vehicles (LV) and heavy vehicles (HV). The variables used are traffic characteristics, namely volume, speed, and density. To determine the formulation of the characteristics relationship, three models are used, among others Greensield, Greenberg, and Underwood.From the results of the study concluded that the Greenshield model is the best model with the value of R ² = 0.99 with a mathematical equation the relationship of speed-density, volume-density, and volume-speed as follows: S = 41,3 -0,15.D, V = 41,3.D-0,15.D², V = 273 . S – 6,6.S².